2016
DOI: 10.1371/journal.pone.0153758
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Non-Classical (CD14+/lowCD16++) Monocytes Is Associated with Increased Albuminuria and Urine TGF-β1 in HIV-Infected Individuals on Stable Antiretroviral Therapy

Abstract: ObjectiveHigh rates of albuminuria are observed among HIV-infected individuals on stable antiretroviral therapy (ART). Though pro-inflammatory and pro-fibrotic responses are described as components of albuminuria in the general population, it is unclear how these responses are associated to albuminuria in ART-treated chronic HIV. We investigated the relationship of monocyte subsets and urine inflammatory and fibrotic biomarkers to albuminuria in ART-treated HIV-infected participants.Design and MethodsCross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…The increased expression of TGF-β1 in persistent renal injury 17 manifests as increased urinary excretion of TGF-β1 18 . This has been documented in renal diseases associated with increase in extracellular matrix production,6, 7 including HIV-related nephropathy 10 . The finding of increased urinary excretion of TGF-β1 in patients with HIV and CKD was corroborated by our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The increased expression of TGF-β1 in persistent renal injury 17 manifests as increased urinary excretion of TGF-β1 18 . This has been documented in renal diseases associated with increase in extracellular matrix production,6, 7 including HIV-related nephropathy 10 . The finding of increased urinary excretion of TGF-β1 in patients with HIV and CKD was corroborated by our study.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies in patients with CKD who are HIV-positive have demonstrated elevated levels of TGF-β1 in renal tissue, 8 serum, 9 and in the urine 10 of patients with HIV-associated nephropathy. Our study aim was to investigate the association of uTGF-β1 with prevalent CKD in HIV-positive patients in Nigeria.…”
mentioning
confidence: 99%
“…Macrophages/monocytes also play important roles in regulatory immunity, such as antigen presenting [4]. Recent studies showed that there are at least two types of macrophages or monocytes, M1 and M2 macrophages [6] or classical/inflammatory and patrolling/regulatory monocytes [7], respectively. M1 macrophages are the "killer" type macrophages, which promote inflammation and rapidly eliminate the pathogens but also cause tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…We do not know whether the correlation found between microinflammation and RRF is a mere association or whether there is a causal link between non‐classical monocytes and RRF loss. In this sense, recent publications point to the fact that these non‐classical monocytes are high in patients infected with the human immunodeficiency virus (HIV) who suffer from albuminuria ( P = 0.034), and their authors have raised the possibility that they could play a role in renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%